Efficacy of a Moderately Low Carbohydrate Diet in a 36-Month Observational Study of Japanese Patients with Type 2 Diabetes - Sanada, Mariko (Nutrients, 2018)
We previously showed that a non-calorie-restricted, moderately low-carbohydrate diet (mLCD) is more effective than caloric restriction for glycemic and lipid profile control in patients with type 2 diabetes. To determine whether mLCD intervention is sustainable, effective, and safe over a long period, we performed a 36-month observational study. We sequentially enrolled 200 patients with type 2 diabetes and taught them how to follow the mLCD. We compared the following parameters pre- and post-dietary intervention in an outpatient setting: glycated hemoglobin (HbA1c), body weight, lipid profile (total cholesterol, low and high-density lipoprotein cholesterol, triglycerides), systolic and diastolic blood pressure, liver enzymes (aspartate aminotransferase, alanine aminotransferase), and renal function (urea nitrogen, creatinine, estimated glomerular filtration rate). Data from 157 participants were analyzed (43 were lost to follow-up). The following parameters decreased over the period of study: HbA1c (from 8.0 ± 1.5% to 7.5 ± 1.3%, p < 0.0001) and alanine aminotransferase (from 29.9 ± 23.6 to 26.2 ± 18.4 IL/L, p = 0.009). Parameters that increased were high-density lipoprotein cholesterol (from 58.9 ± 15.9 to 61.2 ± 17.4 mg/dL, p = 0.001) and urea nitrogen (from 15.9 ± 5.2 to 17.0 ± 5.4 mg/dL, p = 0.003). Over 36 months, the mLCD intervention showed sustained effectiveness (without safety concerns) in improving HbA1c, lipid profile, and liver enzymes in Japanese patients with type 2 diabetes.